Mycotoxins Detection and Fungal Contamination in Black and Green Tea by HPLC-Based Method - K. Pakshir; Z. Mirshekari; H. Nouraei; Z. Zareshahrabadi; K. Zomorodian; H. Khodadadi; A. Hadaegh (Journal of Toxicology)
The fungal contamination and total aflatoxins (AF) and ochratoxin A (OTA) of tea samples were examined. A total of 60 tea samples were extracted and treated with immunoaffinity columns. The amount of AF and OTA were determined by using high-performance liquid chromatography (HPLC) with a fluorescence detector (FD). Tea samples were cultured and the fungi were identified. The results showed that 24 (40%) samples were contaminated with AFs and none of the tea samples were above the acceptable limit of AFs (≥10 μg/kg). All of the samples were contaminated with OTA where only 3 black tea samples (6.6%) and 1 green tea sample (6.7%) were detected to have more than the standard limits of toxin (10 μg·kg−1). The mean concentration of OTA in the black tea was higher than green tea. Aspergillus niger was the predominant fungi isolated from black and green tea samples. Considering the high contamination of mycotoxins in tea samples, regular monitoring in the tea process for improving quality is recommended.